The meaning of the childbirth and of the nursing’s attendance: the view of women in immediate post parturition - Rodrigues, Dafne Paiva; Montesuma, Francisca Gomes; Silva, Raimunda Magalhães da (Rev Rene, 2001)
Study investigates the meaning of the childbirth and of the nursing attendance for women that have gone though lived the delivery in two Public Maternities of Fortaleza-CE. Starting whal from the interviewees’ saud, we visualized that the childbirth was a singular event in your lives, that in spite of the pain, nervousness and fear, it implicated in a personal accomplishment. With relationship to the nursing attendance, all expressed full satisfaction with the provided care, what made it possible was a fast evolution of the childbirth work. We pointed out the need of the professionals of health understanding for the customer’s valorization as a whole, extolling the educational focus in the pre-childbirth, childbirth and post-parturition.